2022
DOI: 10.37808/paq.46.3.4
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study of Pandemic-Induced Telework: Federal Workers Thrive, Working Parents Struggle

Abstract: This study examines the forced transition to telework during the COVID-19 pandemic using qualitative data from two open surveys administered by the Federal News Network in 2020: in the first two months and, then, 10 months into the pandemic. We provide in-depth analysis of 1,969 open-ended comments from 1,589 federal employees collected seven months apart, telling the story of how they continued performing their responsibilities under a full-time telework schedule. Federal employees perceive the transition to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Other researchers who explored acquisition and retention utilized a qualitative process (Cohen et al, 2022;Leung et al, 2022;Lyu et al, 2022;Mullins et al, 2022;Rebmann & Foerst, 2022). Lyu et al (2022) built on previous qualitative studies to explore the effects of recruitment and retention.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Other researchers who explored acquisition and retention utilized a qualitative process (Cohen et al, 2022;Leung et al, 2022;Lyu et al, 2022;Mullins et al, 2022;Rebmann & Foerst, 2022). Lyu et al (2022) built on previous qualitative studies to explore the effects of recruitment and retention.…”
Section: Methodsmentioning
confidence: 99%
“…The data collection process of interviewing management and staff was similar to the method for this study. In the study of multigenerational managers and the effect on retaining a younger workforce, Mullins et al (2022) concluded that a qualitative approach was preferred when exploring nuances or issues of interest to the problem at hand during the global pandemic. If a manufacturing human resource manager does not recognize and prevent these potential issues, then workforce turnover will increase.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Their study accentuated the significance of organizational support for remote work success and to keep remote workers motivated and productive. By creating a conducive remote work culture, proving sufficient ICT collaboration tools, prioritizing the well-being of teleworkers by providing life and work balance, eradicating micromanagement of remote work (Mullins, Scutelnicu & Charbonneau, 2022). These were some of the examples provided to demonstrate how organizations offered support to remote workers to ensure that both the organization and remote workers yield positive outcomes from telework.…”
Section: Organization Factorsmentioning
confidence: 99%